2008
DOI: 10.1088/0953-8984/20/21/215223
|View full text |Cite
|
Sign up to set email alerts
|

The effects of crystallographic orientation and strain on the properties of excitonic emission from wurtzite InGaN/GaN quantum wells

Abstract: We have examined in detail crystal orientation effects on the properties of excitonic emission from wurtzite In x Ga 1−x N/GaN quantum wells (QWs) with piezoelectric polarization using exciton binding and transition energy calculations based on a single-band effective-mass theory. We show numerical results for the bandgaps, effective heavy-hole masses, piezoelectric polarizations and fields, exciton wavefunctions, exciton binding and transition energies and radiative lifetimes of excitonic emission as a functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 68 publications
0
11
0
Order By: Relevance
“…In addition, the ABC model only describes the dynamics of e-h pairs recombination. In our case, the exciton binding energy E b is estimated to be larger than 26 meV due to quantum confinement [24]. As a consequence, even at room temperature (k B T ≈ 26 meV), the influence of excitons needs to be taken into account.…”
Section: Modeling Of Carrier-density-dependent Recombination Dynamentioning
confidence: 76%
See 1 more Smart Citation
“…In addition, the ABC model only describes the dynamics of e-h pairs recombination. In our case, the exciton binding energy E b is estimated to be larger than 26 meV due to quantum confinement [24]. As a consequence, even at room temperature (k B T ≈ 26 meV), the influence of excitons needs to be taken into account.…”
Section: Modeling Of Carrier-density-dependent Recombination Dynamentioning
confidence: 76%
“…where E b0 is the exciton binding energy at low carrier density [24] and n Mott is the 2D critical Mott density, which is about 10 12 cm −2 for GaN-based QWs [20,31]. Since we investigate InGaN QWs with a relatively low In content (<10%), we assume that the critical Mott density remains unchanged.…”
Section: Modeling Of Carrier-density-dependent Recombination Dynamentioning
confidence: 99%
“…With incident light excitation, the excitons effectively form in the InGaN MQW nanorods as the binding energy is significantly larger than the thermal energy. 22 These excitons can diffuse and arrive at the sidewall surface of the nanorods. It has been reported that excitons effectively dissociate at the various heterogeneous interfaces, such as organic semiconductors and perovskites.…”
Section: Resultsmentioning
confidence: 99%
“…There has been a significant debate in the community on the carrier recombination dynamics of InGaN quantum wellswhether it originates from free electron-hole 19 or excitonic recombination. 20,21 Given the large exciton binding energy in InGaN quantum wells due to a strong quantum confinement effect, 22 the presence of both free carriers and excitons should be considered in density dependent carrier dynamics studies, which has recently been suggested. 12,23,24 Even at room temperature, a rapid formation of excitons results in a significant exciton fraction in the total carrier population in InGaN quantum wells, as quantitatively calculated by Hangleiter et al 24 Blancon et al recently 25 proposed that the lower energy states at the layer edges/surface area of perovskite nanoplatelets could directly facilitate exciton dissociation.…”
Section: Introductionmentioning
confidence: 99%
“…The influence of the random cation distribution on the inhomogeneous broadening has been theoretically investigated by Lee and Bajaj for excitons in AlGaAs at low temperature. 29 In 3 nm semipolar InGaN QWs, the exciton binding energy is about 40 meV, 30 considerably larger than the room temperature k B T. Thus, it is reasonable to assume that at low and moderate carrier densities PL at room temperature is dominated by the exciton recombination. Recent studies on AlGaN and InGaN QWs support this assumption.…”
Section: Discussionmentioning
confidence: 99%